Penentuan Harga Opsi Jual Amerika dengan Menggunakan Metode Gerak Brown Geometri - Yuli Andari Wulan; Dony Permana (Journal of Mathematics UNP, 2018)
Abstract– An option is a contract that gives the owner the right to buy or sell a number of instruments that relied upon the contract at a certain price and within the time period specified. There are two types of options that are known, namely call option and put option. Based on execution time, options can be divided into two types, namely the European type options and option types are American. The purpose of this research that is shaping the American Option pricing formula by using the method of geometric Brownian motion. The steps undertaken in this research is studying price movements of stocks, models, and interpret the options pricing models are selling America. Option price is affected by the movement of the stock price, strike price, volatility, the average rate of return (return) stock price, risk-free interest rate, and time to maturity..